Association of meteorological factors with childhood pneumonia incidence in Central Gondar Zone, Northwest Ethiopia: a time-series study (2013–2022) - Lidetu Demoze; Gelila Yitageasu (Italian Journal of Pediatrics)
Abstract Background Childhood pneumonia remains a significant clinical and public health challenge, contributing to substantial morbidity and mortality in under five years of age, including Ethiopia. Despite efforts to reduce its impact, childhood pneumonia persists as a leading cause of death in young children, particularly in low-resource settings. This study investigates the association between childhood pneumonia incidence and meteorological factors in the Central Gondar Zone, northwest Ethiopia, from January 2013 to December 2022. Methods Institution based time-series cross-sectional study design was conducted in Central Gondar Zone, Northwest Ethiopia. Data on childhood pneumonia cases were obtained from the Central Gondar Zone Health Department and Gondar Administrative Health Department. Meteorological data, including temperature, rainfall, and relative humidity, were sourced from the West Amhara Meteorology Agency. Spearman correlation, bivariate negative binomial, and multivariable negative binomial regressions were employed to analyze the relationship between childhood pneumonia incidence and meteorological factors. Results The findings reveal a consistent increase in childhood pneumonia incidence during the study period. Specifically, there is a significant inverse association between mean monthly temperature and the incidence of childhood pneumonia, indicating a higher incidence during the cooler month. In contrast, mean monthly rainfall demonstrates a positive association with childhood pneumonia incidence, suggesting increased incidence following periods of higher rainfall. However, no significant association was observed between relative humidity and childhood pneumonia incidence. Conclusions These results underscore the complex interplay between meteorological factors and childhood pneumonia incidence, with implications for public health interventions and climate adaptation strategies in Ethiopia. Understanding these associations can inform targeted interventions to mitigate the impact of childhood pneumonia, particularly in climate-vulnerable regions.